Tissue and cell donation for articular cartilage tissue engineering experimentation from Islamic perspective - Hashi, Abdurezak Abdulahi; Ahmad Radzi, Muhammad Aa'zamuddin; Mohd. Azharuddin, Nur Syamimi; Azhim, Azran; Sha'ban, Munirah (UKM Medical Centre, 2018)
Since the advancement of tissue engineering has reached the muslim world including Malaysia, muslim jurists and ethicists, like their counterparts around the world, were concerned about the ethical and social implications of tissue engineering practices. It is worth mentioning that Muslim jurists and ethicists did not exhibit any form of antiscientific advances in this field, however they have raised genuine concerns about the safety of life in the face of these advances. The technology has been developed with the objective of repairing the damage tissues or organs by combining cells, engineering and materials technique, as well as bio- and physico-chemical stimuli. Experimentation in tissue engineering is important before the technology can advance from bench side (laboratory) to bedside (clinical application), however, the scientific procedures must be guided by the norms morality. This include articular cartilage tissue engineering in which one way of harvesting cell sources in its experimentation was to take from the human patients. It has been identified that there were studies using cells harvested from human tissue, for instances, chondrocytes and mesenchymal stem cells, for in vitro (monolayer and 3 dimensional constructs) as well as in vivo which the constructs were implanted in immunodeficient animal models. Muslim jurists are concerned whether these practices ovulate ethical values or otherwise. The paper uses analytical method and aims to study Muslim jurists’ opinion on the moral and social concerns related to cell and tissue donation for experimentation through and within the Islamic perspective. The study reviews the latest scientific practices related to cell and tissue engineering and consults the founding sources of Islamic ethics and the Muslim jurists’ opinion on given matters in this field. The paper though does not intend to issue any fatwa on the permissibility of these scientific practices or otherwise, rather it aims to unveil Muslim jurists and ethicists opinions on these practices.